Analysis of Managerial Leadership on Improving the Quality of Hospital Services Through Patient Safety Culture at dr. Darsono Hospital, Pacitan, East Java - Trisnawati, Dwi Ayu; Wardani, Ratna; Farida, Siti (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: Patient safety is an important issue because of the large number of medical error cases that occur in various parts of the world. Patient safety culture is the first step in developing safety because it contains values, attitudes, competencies, and behavioral patterns that determine patient safety programs. The aim of this research is to analyze the influence of managerial leadership on improving the quality of hospital services through a patient safety culture.Subjects and Method: This was a quantitative study with an explanatory approach. The population used was health workers at Dr. Darsono Hospital, as many as 240 people. Based on the proportionate stratified sampling technique, a sample of 148 people was obtained. This research consists of independent variables and dependent variables. Independent variable is managerial leadership and the dependent variables are patient safety culture and hospital service quality. The data was then analyzed using SEM PLS.Results: The results of the analysis show that managerial leadership has a significant effect on patient safety culture and improving service quality (p<0.001), patient safety culture has a significant effect on improving service quality (p<0.001), and patient safety culture can mediate the relationship between managerial leadership and service quality (p<0.001). The values of the patient safety culture determination coefficient of 64.9% and the service quality variable of 80.9% showed both variables influenced this study; the remaining 35.1% and 19.1% were explained by other variables outside the study model.Conclusion: Patient safety culture at Dr. Darsono Hospital is in the sufficient category; a managerial leadership role is needed to improve the implementation of patient safety culture so that the quality of hospital services can increase optimally.